The Effect of Live Yeast (Saccharomyces cerevisiae) on Milk Yield of Crossbred Dairy Cattle at Khumaltar, Nepal - Acharya, B.; Dhital, B. (Journal of the Institute of Agriculture and Animal Science, 2018)
A study was carried out to assess the effect of live yeast Saccharomyces cerevisiae (Nutriferm™) on milk production at National Cattle Research Program Khumaltar Lalitpur from 19 March 2015 to 15 April 2015. Twenty crossbred cattle were selected randomly and divided into five treatment groups. Each group had four animals arranged in Complete Randomized Design (CRD). Among five treatment groups, treatment (T1) was treated with 0.5 kg/MT of live yeast Saccharomyces cerevisiae (SC) incorporated feed, treatment (T2) with 1 kg/MT SC, treatment (T3) with 1.5 kg/MT SC, treatment (T4) with 2 kg/MT SC and treatment (T5) as control without any live yeast inclusion in feed. Supplementation of the live yeast up to seventh day of the trial had statistically non-significant (P>0.05) effect on average milk yield per cattle between the treatments. Response of the yeast on mean milk yield per cattle between the treatments was found statistically different (P<0.05) on fourteenth day and twenty-eight day of the trial. On fourteenth day mean milk yield of control group (T4) was statistically significant with highest dose rate inclusion T4 only but remained non-significant with the rest of the lower dose rate treatments. With further supplementation of the yeast up to 28th day of the trial results showed the statistically significant effect with lower dose rate T2 as well with respect to control group besides T4. Hence, the result of this experiment indicates that supplementation of live yeast for at least 14 days has role in the enhancement of milk production in crossbred dairy cattle with faster effect by dose rate of T4 treatment.